Learning of Tales in Indonesian Literature to Develop Early Children's Language Ability - Masruroh, Umi (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Language development for early childhood is important to make it easier for children to interact with people around them. The purpose of this research is to identify the development of language skills in early childhood through learning fairy tales. This research was conducted at RA Diponegoro Adisara, Jatilawang District, Banyumas Regency. Subjects in the study amounted to 30 children consisting of 15 boys and 15 girls. The type of research used is descriptive qualitative. Data collection techniques by way of observation, interviews and documentation. Data analysis techniques used by collecting data, reducing data, presenting data and concluding. Based on the results of the research and discussion, it can be concluded that learning fairy tales in Indonesian literature is an effective way to develop early childhood language skills. Storytelling learning has great benefits in language development in early childhood. In this lesson, children can learn through interesting stories that come from the nation's traditions and culture. Some of the benefits of learning storytelling for language development in early childhood include: increasing language intelligence, training memory sharpness, honing speaking skills, adding new vocabulary, and teaching emotional and social intelligence. Therefore, teaching storytelling can support communication and language development in early childhood in a fun and effective way.